LH supplementation of ovarian stimulation protocols influences follicular fluid steroid composition contributing to the improvement of ovarian response in poor responder women - S. Marchiani (Nature Portfolio, 2020)
Abstract In this prospective study, we evaluated the steroid levels in 111 follicular fluids (FF) collected from 13 women stimulated with FSH monotherapy and 205 FF collected from 28 women stimulated with FSH + LH because of a previous history of hypo-responsiveness to FSH. Steroid levels were measured by HPLC/MS–MS and related to ovarian stimulation protocol, oocyte maturity, fertilization and quality of blastocysts, after individually tracking the fate of all retrieved oocytes. 17-Hydroxy-Progesterone, Androstenedione, Estradiol and Estrone were significantly higher in the FSH + LH protocol. Progesterone, 17-Hydroxy-Progesterone and Estradiol were more expressed in FF yielding a mature oocyte (p < 0.01) in the FSH + LH protocol. FF Progesterone concentration was correlated with the rate of normal fertilization in the FSH protocol. None of the FF steroids measured were associated with blastocyst quality and achievement of pregnancy. Our results indicate that LH supplementation in hypo-responsive women modifies ovarian steroid production, mimicking physiological production better and likely contributing to an improved ovarian response. Employing a correct methodological procedure to evaluate the relationship between FF steroid hormones and assisted reproduction outcomes, our study reveals that some steroids in single follicles may be helpful in predicting oocyte maturity and fertilization.